Rehabilitation and strengthening of high-strength rectangular CFST beams using a partial wrapping scheme of CFRP sheets: Experimental and numerical study. (May 2017) - Al Zand, Ahmed W.; Badaruzzaman, Wan Hamidon W.; Mutalib, Azrul A.; Hilo, Salam J.
Abstract: Recently, concrete-filled steel tubular (CFST) members are becoming highly recommended by engineers for use in composite structures. Lately, carbon fiber-reinforced polymer (CFRP) composite materials have been used for strengthening steel and CFST flexural members. Both experimental and numerical studies are adopted in this research to further investigate the behavior of various sections of rectangular CFST beams strengthened and/or repaired with unidirectional CFRP sheets. The effects of the U-shaped wrapping scheme using multiple CFRP layers applied at various beam lengths was studied. In general, the results demonstrated that the moment capacity of strengthened CFST beams increased significantly with increasing CFRP layers; for example, it increased by approximately 40% and 55% for beams with compact and slender sections, respectively, when wrapped with 4 CFRP layers. The capacity of damaged CFST beams has improved over 65% when repaired with 2 CFRP layers. Moreover, the effects of wrapping the beam along 75% of its length achieved a similar enhancement ratio and behavior as that of the beam with wrapping along 100% of its length for the same CFRP layers. Highlights: Partial CFRP wrapping scheme was used to rehabilitate the CFST beams. CFST beams' capacity increased more than 20% when strengthened with CFRP sheets. Repairing the damaged CFST beam by CFRP improved its capacity and ductility more than 60%. The effects of 75% wrapping length achieved the same improvements of 100% wrapping length. Beams with non-compact sections show the best enhancement with the increasing of CFRP layers.